2011
DOI: 10.1108/00035591111097657
|View full text |Cite
|
Sign up to set email alerts
|

Study of anticorrosion and microwave absorption properties of NiZn ferrite pigments

Abstract: Purpose -The purpose of this paper is to report the electrochemical verification of anticorrosive properties of NiZn ferrites as pigments in protective coatings and evaluation of their microwave absorbing properties. Design/methodology/approach -Ferrites, represented by formula Ni x Zn (12 x) Fe 2 O 4 , where x ¼ 0, 0.2, 0.4, 0.6, 0.8, 1.0, were synthesized using a ceramic method. The samples of ferrites were examined by X-ray diffraction and SEM. Immersion tests in ferrite extracts, combined with electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…The impedance data showed that the anticorrosion mechanism of ferrites in coatings is associated with the formation of porous, insoluble precipitates of hydroxides over cathodic sites. The partial blocking of the cathodic sites decreases the cathodic current and, in this way, reduces the overall corrosion (Miszczyk and Darowicki, 2011). The impedance response in the Nyquist plots consisted of characteristic semicircles.…”
Section: Resultsmentioning
confidence: 99%
“…The impedance data showed that the anticorrosion mechanism of ferrites in coatings is associated with the formation of porous, insoluble precipitates of hydroxides over cathodic sites. The partial blocking of the cathodic sites decreases the cathodic current and, in this way, reduces the overall corrosion (Miszczyk and Darowicki, 2011). The impedance response in the Nyquist plots consisted of characteristic semicircles.…”
Section: Resultsmentioning
confidence: 99%
“…sol. of NZF develop the local anodic site at the center and a cathodic site near the edge of drop and 20,21) . The mechanism of forming these sites was explained by Evan 22) .…”
Section: Resultsmentioning
confidence: 99%
“…Ferrite pigments with spinel structure have been studied for decades; their general formula is MFe 2 O 4 , where M is a divalent metallic ion (Miszczy and Darowicki, 2011). Ferrites are known to possess high hardness, high coverage power, high coloration and insolubility.…”
Section: Introductionmentioning
confidence: 99%